Odpowiedzi

  • Użytkownik Zadane
2010-01-10T15:49:56+01:00
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42 /:7
23y-11x=-32

x+y=6
23y-11x=-32

x=6-y
23y-11(6-y)=-32

x=6-y
23y-66+11y=-32

x=6-y
34y=-32+66

x=6-y
34y=34 /:34

x=6-y
y=1

x=6-1
y=1

x=5
y=1
2010-01-10T15:53:20+01:00
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42 /:7
-11x+23y=-32

x+y=6
-11x+23y=-32

z pierwszego równania wyliczamy, że y=6-x, podstawiamy do drugiego otrzymując:

-11x+23(6-x)=-32
-11x+138-23x=-32
-34x=-170
x=5
y=6-x=6-5=1
2010-01-10T16:00:47+01:00
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

(obliczamy Y)
7x+7y=42|*11
-11x+23y=-32|*7

77x+77y=462
-77x+161y=-224

77y + 161y= 238
238y=238| :238
Y=1
(obliczamy X)
7x+7y=42|*23
-11x+23y=-32| *(-7)

161x+161y=966
77x - 161y=224

238x=1190|:238
X=5



X=5
Y=1